Environmental impact of nanomaterials in composite membranes: Life cycle assessment of algal membrane photoreactor using polyvinylidene fluoride – composite membrane. (20th November 2018) - Chong, Woon Chan; Chung, Ying Tao; Teow, Yeit Haan; Zain, Masniroszaime Md; Mahmoudi, Ebrahim; Mohammad, Abdul Wahab
Abstract: This study assessed the environmental impacts of a composite polyvinylidene fluoride (PVDF) membrane (incorporating nanomaterials) and compared with neat PVDF membrane on algal membrane photoreactor (A-MPR) system's overall sustainability. The life cycle assessment (LCA) was carried out using Simapro 8.4.0 with cradle-to-gate approach, including raw materials, equipment, transportation and electricity consumption using ReCiPe 1.13 (H) and IPCC 2013 GWP 100a methodology. From the LCA analysis, silver/graphene oxide - polyvinylidene fluoride (Ag/GO-PVDF) membrane fabrication showed higher environmental impact than the neat PVDF membrane fabrication due to the addition of Ag/GO nanohybrids into the polymer. However, the A-MPR system using the Ag/GO-PVDF membrane exhibited better environmental footprint due to the improved performance of the modified membrane in producing higher volume of permeate as the output. Therefore, the A-MPR system using Ag/GO-PVDF membrane had outweighed the additional environmental impact of the Ag/GO-PVDF membrane fabrication process. Energy demand was identified as the main environmental hotspot in the LCA analysis. Subsequently, sensitivity analysis was performed to find out the effect of various energy mix for electricity generation towards the environment. The analysis revealed that the energy source for electricity generation had significant influence on the overall sustainability of the A-MPR system. The use of grid with 100% renewable energy (hydropower and geothermal) and solar photovoltaic might be able to mitigate 94.8% and 97.5% of CO2 emission, respectively. Highlights: Fabrication of composite membrane had greater environmental influence. Composite membrane showed lower environmental footprint in the reactor operation. Reduction of electricity usage is essential to minimize the environmental impact. Development of green energy source is crucial to reduce environmental loads.